Do community‐dwelling Māori and Pacific peoples present with dementia at a younger age and at a later stage compared with NZ Europeans?. (15th May 2018) - Cullum, Sarah; Mullin, Katherine; Zeng, Irene; Yates, Susan; Payman, Vahid; Fisher, Mark; Cheung, Gary
Abstract : Objective: Ethnicity may affect presentation to clinical services in people with dementia; however, no studies have examined this in Māori or Pacific peoples in New Zealand (NZ). Our objective was to examine the routinely collected clinical data from a memory assessment service in South Auckland to examine the presentation of dementia in the major NZ ethnic groups. Methods: A total of 360 patients presenting to a memory service with a new diagnosis of dementia were included in this study. Demographic data (age, sex, and ethnicity) and dementia sub‐type and severity were analyzed. Results: There were 142 NZ European (mean age: 79.2, SD 7.4), 43 Māori (mean age: 70.2, SD 7.6), 126 Pacific (mean age: 74.3, SD 7.6), and 49 other ethnicities (mean age: 78.0, SD 8.5) presenting with a new diagnosis of dementia. After adjustment for gender and dementia subtype, Māori and Pacific patients were 8.5 and 5.3 years younger than NZ European patients ( P  < 0.0001). Pacific peoples tended to present with more advanced dementia (OR = 1.63, 95% CI: 0.98–2.70, P  = 0.06) after adjustment for age and gender. There was little difference in the subtypes of dementia between ethnic groups. Conclusions: Māori and Pacific peoples with dementia presented to an NZ memory service at a younger age than NZ Europeans, and Pacific peoples presented with more advanced dementia. A population‐based epidemiological study is critical to determine whether Māori and Pacific peoples have indeed a higher risk of developing dementia at a younger age.